Reading and Comprehension at the Beginning of Secondary School: Contributions for Educational Guidanc - Zabaleta, Verónica (2017)
This paper develops the preliminary results of an ongoing research project that aims to characterize programs and proposals for intervention in reading comprehension (RC) and compare them with teaching practices in the first year of secondary education. Specifically, we discuss the program Leer para Comprender (Read to Understand), the program LEE Comprensivamente (READ Comprehensively), and the institutional frameworks of Reciprocal Teaching and the Cultural Mediational Model for Improving Reading: Question-Asking-Reading. In addition, some of the axes that can be derived from the analysis of the literature consulted are synthetized, such as: the importance of fluency in RC, the relevance of learning from the text, comprehension as a multi-componential phenomenon, and the importance of social interactions in the programs analyzed. The differences between the modalities presented by the proposals are explained, as well as their limitations in relation to the challenges involved in the management of progressively more complex texts and of a disciplinary nature in secondary education. Finally, we analyze the implications of the intervention in RC for educational guidance.